A job task analysis of the authorised firearms officer – counter terrorism (AFO-CT) national role profile. - Powell, Steven D.; Hogan, Joseph; Fallowfield, Joanne L.; Brown, Pieter E.H.; Tsang, Fiona; Fisken, Alison; Rowland, Daniel; Richards, Lana; Allsopp, Adrian J. (Work, 2024)
BACKGROUND: The Ministry of Defence Police recognised the requirement to develop a Physical Employment Standard (PES) for the Authorised Firearms Officer –Counter Terrorism (AFO-CT) role profile. OBJECTIVE: The purpose of this study was to conduct a job task analysis to identify the most critical and physically demanding tasks performed by AFO-CT personnel. METHODS: A focus group and online survey were undertaken to identify a list of job tasks. The down-selected job tasks were objectively monitored during training events to determine the most physically demanding tasks. Tasks were ranked by physical demand and additional factors (e.g., operational load, primary physical actions). Down-selected tasks were then included in a Subject Matter Experts (SME) task scenario generation workshop. The physiological demands of the resulting standardised scenarios were determined. RESULTS: The focus group (n = 11) identified 13 physically demanding and critical role-related tasks. The subsequent survey (n = 907) down-selected eight tasks with a 'moderate' demand or greater. Thirty AFO-CT personnel completed the eight tasks as part of routine training events. From the observed tasks, four tasks were down-selected and combined into two operationally relevant, reasonable worst-case standardised scenarios during a SME workshop. The two scenarios, 'Conduct Armed Search in the Open for an Active Shooter' and 'Victim Focussed Emergency Search' were used in subsequent phases of the research to form the basis of the AFO-CT PES. CONCLUSION: This research elucidated the most physically demanding job tasks within the AFO-CT role profile to inform the development of a MOD armed policing PES.